Cutaneous leishmaniasis in mast cell-deficient W/Wv mice. - Katakura, K (1993)
Genetically mast cell-deficient W/Wv mice infected with Leishmania amazonensis showed progressive development of ulcerative skin lesions. However, no significant differences between the W/Wv mice and the normal littermates with respect to size of the lesions, anti-Leishmania immunoglobulin E antibody, and the number of eosinophils accumulated in the lesions were observed.